PEMASARAN SUSU DI KECAMATAN MOJOSONGO DAN KECAMATAN CEPOGO, KABUPATEN BOYOLALI - Puteri Utami Lintang Premisti; A Setiadi; W Sumekar (MEDIAGRO, 2016)
The purpose of this research is to determine the marketing channels, marketing marjin and marketing efficiency in the marketing of milk in Mojosongo District and Cepogo District. The Method use in this research was a survey method. Determination of the sample of respondents is done by purposive method is to choose a district that has the largest livestock population in Boyolali. Determination of respondents to represent the population conducted by slovin. The number of samples was 66 respondents. The result of this research showed that there were two patterns of fresh milk marketing channels. Channel I: dairy farmers     whole sale      marketing agencies (KUD). Channels II: dairy farmers              marketing agencies (KUD). Marketing marjins in Mojosongo District IDR. 1,200 / lt, channel II IDR. 900 / lt and Cepogo District IDR. 600 / lt. farmer's share in Mojosongo District channel I by 84%, second channel 91%, and Cepogo District by 87%.   Keywords: farmer’s share, marketing channels, marketing efficiency, marketing marjin